LKB1 Regulates Goat Intramuscular Adipogenesis Through Focal Adhesion Pathway - Xiong, Yan; Wang, Yuxue; Xu, Qing; Li, An; Yue, Yongqi; Ma, Yan; Lin, Yaqiu (Frontiers in Physiology, 2021)
Intramuscular fat (IMF) deposition is one of the most important factors to affect meat quality in livestock, and induce insulin resistance and adverse metabolic phenotypes for humans. However, the key regulators involved in this process remain largely unknown. Although liver kinase B1 (LKB1) was reported to participate in the development of skeletal muscles and classical adipose tissues. Due to the specific autonomic location of intramuscular adipocytes, deposited between or within muscle bundles, the exact roles of LKB1 in IMF deposition need further verified. Here, we cloned the goat LKB1 coding sequence with 1317 bp, encoding a 438 amino acid peptide. LKB1 was extensively expressed in detected tissues and displayed a trend from decline to rise during intramuscular adipogenesis. Functionally, knockdown of LKB1 by two individual siRNAs enhanced the intramuscular preadipocytes differentiation, accompanied by promoting lipid accumulation and inducing adipogenic transcriptional factors and triglyceride synthesis related genes expression. Conversely, overexpression of LKB1 restrained these biological signatures. To further explore the mechanisms, the RNA-seq technique was performed to compare the difference between siLKB1 and control group. There were1043 differential expression genes (DEGs) were screened, including 425 up-regulated genes and 618 down-regulated genes in the siLKB1 group. The KEGG analysis predicted that the DEGs were mainly enriched in the focal adhesion pathway and its classical downstream signal, the PI3K-Akt signaling pathway. Specifically, knockdown of LKB1 increased the mRNA level of FAK and vice versa in LKB1 overexpressed cells, a key component of the activated focal adhesion pathway. Convincingly, blocking this pathway by a specific FAK inhibitor (PF573228) rescued the observed phenotypes in LKB1 knockdown adipocytes. In conclusion, LKB1 inhibited goat intramuscular adipogenesis through the focal adhesion pathway. This work expanded the genetic regulator networks of IMF deposition and provided theoretical support for improving human health and meat quality from the aspect of intramuscular fat deposition.